Gut Microbial Signature of Hepatocellular Cancer in Men With Cirrhosis. Issue 5 (30th April 2021) - Albhaisi, Somaya; Shamsaddini, Amirhossein; Fagan, Andrew; McGeorge, Sara; Sikaroodi, Masoumeh; Gavis, Edith; Patel, Samarth; Davis, Brian C.; Acharya, Chathur; Sterling, Richard K.; Matherly, Scott; Fuchs, Michael; et al.
Abstract : The gut microbiome is altered in cirrhosis. Recent evidence has suggested a key role for the gut microbiota in the progression of cirrhosis and the development of hepatocellular carcinoma (HCC). We studied the differences in the microbial composition in patients with cirrhosis with prior and future HCC in the context of other complications (eg, infections, hepatic encephalopathy). The following 2 cohorts were recruited prospectively: the prior HCC cohort, in which outpatients with HCC within 2 years were age‐matched, sex‐matched, and Model for End‐Stage Liver Disease (MELD) score–matched with those without HCC; and the future HCC cohort, in which patients were followed for 2 years and divided into future HCC versus no HCC after age, sex, and MELD‐score matching and other complications were also recorded. Microbiota composition and predicted function were analyzed with ribosomal RNA sequencing and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PiCRUST)and compared between (1) prior HCC versus none and (2) future HCC versus none, and in the future cohort, comparisons were also made between those patients who developed (1) HCC only versus without complications, (2) HCC only versus non‐HCC complications only, and (3) HCC + other complications versus non‐HCC complications only. A total of 142 men (76 total in the prior cohort [38 with/38 without HCC] and 66 total in the future cohort [33 with/33 without future HCC]) were included. The groups had similar etiology, lactulose/rifaximin/proton pump inhibitor use, diabetes mellitus, and non‐HCC complications. Microbial diversity was similar between prior HCC/not or future HCC/not. On DESeq2 higher Clostridium sensu stricto and Anaerotruncus were significantly associated with protection from HCC, whereas the reverse was seen with Raoultella and Haemophilus regardless of prior/future HCC comparisons. Functions focused on urea cycle, bioenergetics, tryptophan, and toluene metabolism were different between the groups. Rothia was specific for other complications. Despite age, sex, and MELD‐score matching and accounting for other complications, gut microbiota composition and the predicted function are different in men with cirrhosis with and without prior HCC and can be extended toward future HCC development.